Error analysis in master’s theses by non-Arabic speakers in International Islamic University Malaysia = تحليل الأخطاء في رسائل الماجستير لدارسي العربية الناطقين بغيرها في الجامعة الإسلامية العالمية بماليزيا - Hamawia, A, Adham Hamawia; Wan Ahmad, Wan Rusli; Altabaa, Homam; Ahmad H.Osman, Rahmah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
One of the key characteristics of academic writing is its precision in expressing facts and ideas, along with its avoidance of subjective impressions, rhetorical styles, and ambiguous formulations. It is a skill that every researcher must acquire and master. The foundation of this skill is sustained reading, particularly within one's field of specialization. When specialized reading is strong, academic writing tends to be strong as well. Conversely, weakness in academic writing may result in some completed theses remaining confined to the shelves of their authors or the universities to which they were submitted, never finding their way to publication. This issue is especially pronounced when students write their theses in foreign languages, as proficiency in a foreign language is essential for high-quality academic writing. Without such proficiency, numerous errors maybe found in the theses, undermining the students’ efforts. Considering this, the study adopted a descriptive-analytical approach to quantitatively and qualitatively analyse the writing errors found in six master's theses completed by students at the International Islamic University Malaysia. Among the study’s key findings is that language is the most suitable domain for applying the criterion of right and wrong. It also found that writing errors stem from two main sources: internal within the language itself, and external arising from other languages. Moreover, these errors may intersect or overlap.